2020
DOI: 10.1021/acs.energyfuels.0c03466
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Characterization of Thin Films at Oil/Water Interfaces and Implications to Emulsion Stability

Abstract: This study provides the first nanoscale characterization of the thin films responsible for oil/water emulsion stability using Transmission Electron Microscopy (TEM). High-resolution images revealed that they are on average 2.5 μm large and 24 nm thick in toluene and can easily fold and wrinkle. The films consisted of vertical stacks of wormlike asphaltene clusters with a thickness of 2.5–9 nm and a length-to-thickness aspect ratio of about 5. These clusters resulted from the aggregation of the most interfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…The kinetical stability of water-in-oil emulsions is mainly attributed to the formation of an interfacial film or elastic layer at the oil−water interface by indigenous surface-active agents in the crude oil 1 including asphaltenes. 1,[7][8][9][10][11][12][13]15,16 Aspects of increased emulsion stability due to asphaltenes have been investigated 1,8,12,13,15,16 (also see ref 18 and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The kinetical stability of water-in-oil emulsions is mainly attributed to the formation of an interfacial film or elastic layer at the oil−water interface by indigenous surface-active agents in the crude oil 1 including asphaltenes. 1,[7][8][9][10][11][12][13]15,16 Aspects of increased emulsion stability due to asphaltenes have been investigated 1,8,12,13,15,16 (also see ref 18 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of emulsion stability due to asphaltenes have been studied. 1,8,12,13,15,16,18 Stable emulsions are formed in oils with high asphaltene fraction, because of the affinity of the asphaltenes to the interface. 1,8,12,13,26 Asphaltenes are defined by a solubility classification, not by chemical structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The promoting effect of polar molecules such as asphaltene and resin on the formation and stabilization of oil-water emulsion has been confirmed in many experiments. Goual et al used a transmission electron microscope to characterize the oil-water interface film at nanoscale and found that the thin film consisted of vertically accumulated wormlike clusters of asphaltene, and one side of the film was rough and hydrophobic, while the other side was smooth and hydrophilic [12]. Rocha et al extracted different types of asphaltenes to prepare emulsions and tested their stability.…”
Section: Introductionmentioning
confidence: 99%